Active aerodynamics control of simplified vehicle body in a crosswind condition. Issue 14 (2nd November 2020) - Nakashima, Takuji; Yan, Chao; Moriuchi, Takashi; Kohri, Itsuhei; Mutsuda, Hidemi; Doi, Yasuaki
Abstract : In this study, the authors used a steady jet from a slit nozzle to control the bi‐stable aerodynamics of a simple vehicle model under crosswind conditions. In general, the aerodynamic coefficients of an automobile change continuously with variations in the relative wind direction (i.e. yaw angle). However, some vehicles show a significant change in their aerodynamics at a certain yaw angle because their wake flow structure changes at that yaw angle. Furthermore, around that critical yaw angle, their aerodynamics sometimes show bi‐stability in which both the wake structures before and after the change are stable. The investigated model is the famous simplified model in vehicle aerodynamic research known as the Ahmed model. Its slant angle was set at 32° as a configuration that causes bi‐stability at a specific yaw angle range larger than 6°. The active aerodynamic control method was demonstrated in both the model scale wind tunnel test and computational fluid dynamics analysis. The slit jet with 18% of the main flow velocity successfully changed the wake flow structure. This showed that it is possible to improve the aerodynamic characteristics.